2006
DOI: 10.1021/pr050449x
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of Protein Tyrosine Phosphatase Activity with Ultra-Sensitive Fluorescent Probes

Abstract: Protein tyrosine phosphatases (PTPs) consist of a large family of enzymes known to play important roles in controlling virtually all aspects of cellular processes. However, assigning functional significance of PTPs in normal physiology and in diseases remains a major challenge in cell signaling. Since the function of a PTP is directly associated with its intrinsic activity, which is subject to post-translational regulation, new tools are needed to monitor the dynamic activities of PTPs, rather than mere abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…This trapping device has previously been used to probe protein tyrosine phosphatase activity. [23][24][25][26][27] Upon ATXmediated cleavage of the phosphodiester bond in the probe, the released intermediate undergoes rapid 1,6-elimination of the fluoride and generates a reactive quinone methide species that, in turn, traps nearby nucleophiles in the ATX active site; this results in covalent labelling of ATX in an activity-dependent manner. Incorporation of a fluorescent dye allows visualisation of active ATX.…”
Section: Probe Designmentioning
confidence: 99%
“…This trapping device has previously been used to probe protein tyrosine phosphatase activity. [23][24][25][26][27] Upon ATXmediated cleavage of the phosphodiester bond in the probe, the released intermediate undergoes rapid 1,6-elimination of the fluoride and generates a reactive quinone methide species that, in turn, traps nearby nucleophiles in the ATX active site; this results in covalent labelling of ATX in an activity-dependent manner. Incorporation of a fluorescent dye allows visualisation of active ATX.…”
Section: Probe Designmentioning
confidence: 99%
“…These probes have been linked to either a biotin tag (66) that allows for purification and/or visualization, or to fluorescent lissamine rhodamine B (67). BBP probes irreversibly inactivate a variety of PTPs, including cytosolic PTPs YopH, PTP1B, HePTP, PTPH1, and SHP-2, transmembrane PTPs LAR, PTPa, and DEP-1, dual-specificity PTPs (DUSPs) VHR, PRL-3, and CDC14, and the low-molecular-weight PTPs (LMPTP or LMW-PTP), but do not bind to alkaline phosphatases, prostatic acid phosphatase, Ser/Thr phosphatases, SH2 or PTB domains, SRC kinase, serine proteases, metalloprotease thermolysin, the cysteine proteases calpain and papain, glyceradehyde-3-phosphate dehydrogenase, GST, lysozyme, or the entire E. coli proteome (66,67). Covalent binding of the probes to PTPs was confirmed by western blotting for biotinylated PTPs or by in-gel imaging of PTP fluorescence, and by mass spectrometry.…”
Section: In-lysate Methodsmentioning
confidence: 99%
“…For example, BBP probes were used to demonstrate that four PTPs showed anomalous activity/expression in lysates of the MCF-7 breast cancer cell line compared with lysates of the human telomerase reverse transcriptase immortalized mammary epithelial cell line (67). Interestingly, when a sideby-side comparison of a fluorescently imaged versus a Coomassie blue-stained gel of the same lysates treated with the fluorescent BBP probe was performed to assess PTP activities in a panel of cancer cell line lysates, differences in PTP activity were revealed that were not evident in the Coomassie blue staining of total protein in the crude lysates.…”
Section: In-lysate Methodsmentioning
confidence: 99%
“…However, the highly unstable nature of the probe renders it impractical for widespread applications in ABPP. [28] Probes based on phenyl vinyl sulfone/sulfonates (20) are another class of PTP probes that were recently developed, [29] but they are likely cross-reactive toward other classes of enzymes that also possess nucleophilic cysteine residues, that is, cysteine proteases. In a most recent example, we developed peptidebased ABPs for PTP by incorporating a novel pTyr mimic, 2-FMPT (21), into suitable peptide sequences.…”
Section: Abps For Protein Phosphatases and Kinasesmentioning
confidence: 99%